Esophageal foreign body removal under holmium laser-assisted gastroscope: A case report - Yang, Zhe; Qin, Shanyu; Li, Xiaomin (Frontiers in Surgery, 2023)
As a common clinical emergence, esophageal foreign body can lead to esophageal perforation followed by severe complications including aortic injury, mediastinal abscess and airway obstruction, leading to a high rate of mortality. Therefore, fast and effective diagnosis and treatment are of great necessity. In this case, holmium laser-assisted gastroscopy was adopted to remove the foreign body incarcerated in the esophagus, allowing patients to avoid traumatic and costly surgeries. It is a supplement to traditional methods of foreign body removal. The new combination tried in this report can bring development and innovation inspiration to the development of endoscopic technology.